Ladderization of polystyrene derivatives by palladium-catalyzed polymer direct arylation. Issue 21 (2nd May 2019) - Takagi, Koji; Tanaka, Hidetoshi; Mikami, Koichiro
Abstract : Pseudo-ladderized polystyrenes could be obtained in high yield by the palladium-catalyzed polymer direct arylation using poly(2-bromostyrene) as a prepolymer. Abstract : Ladderization of polystyrene derivatives successfully proceeded by palladium-catalyzed polymer direct arylation in the presence of a phosphine ligand and pivalic acid using poly(2-bromostyrene) as a prepolymer, in which the polymer tacticity had little influence on the reaction efficiency. The reaction mechanism was supported by theoretical calculation in detail. The optical and thermal properties of pseudo-ladderized polystyrene suggested enhanced chain rigidity.